Device-independent quantum key distribution beyond qubits - Javier Rivera-Dean; Anna Steffinlongo; Neil Parker-Sánchez; Antonio Acín; Enky Oudot (New Journal of Physics)
Device-independent quantum key distribution (DIQKD) aims to generate secret keys between two parties without relying on trust in their employed devices, imposing strict constraints on the experimental conditions needed for successful key generation. In this study, we derive bounds for noise and detection efficiency—two critical parameters for experimental implementations—beyond qubit-based protocols. Our results show that while lower bounds indicate no improvement in noise resilience with increased dimensionality, upper bounds reveal marginal, albeit insignificant, enhancements. Given the experimental challenges associated with the development of qudit-based systems, our findings prompts a debate on their practical utility for DIQKD.